Cerebral toxoplasmosis after renal transplantation. Case report and review. - Da Cunha, Saraiva (1994)
Infection caused by Toxoplasma gondii is a frequent event in Portugal. When this occurs in immunocompetent individuals, it is rarely a matter of concern; the contrary occurs with immunosuppressed patients or in pregnancy. Transplant patients are treated with immunosuppressive drugs which mainly disturb their mechanisms of cellular immunity, and that opens the way to infections by opportunistic intracellular microorganisms. We recently treated a renal transplant patient who suffered from cerebral toxoplasmosis, and this provided an opportunity for a review of the other 20 patients reported in medical literature to date.